The Evolution of American Women’s Studies - Ginsberg, A. author. aut Link
XIV, 239 p.
Keywords: This book is comprised of reflections by diverse women's studies scholars, focusing on the many ways in which the field has evolved from its first introduction in the University setting to the present day.